Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1002/1097-0142(19930915)72:6<1909::aid-cncr2820720619>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Epidermotropic metastatic melanoma are the current histologic criteria adequate to differentiate primary from metastatic melanoma?

Abstract: A case is reported of a patient with a lentiginous acral melanoma of the heel that was excised and recurred 3 years later at the margin of the previous scar. After another 3 years, a group of five small lesions appeared in the thigh that were considered to be junctional and epidermotropic metastases. The authors question the current histologic criteria for differentiating junctional and epidermotropic metastases of previous melanomas from multiple primary melanomas. It is concluded that the clinical history is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
2
24
1
Order By: Relevance
“…Eleven of these markers map to 8 different chromosomes and have previously shown a high incidence of LOH or MSI (>30%) either in primary or metastatic melanomas (35,46-48): D1S214 (1p36.3), D2S2182 (2p16), D2S2291 (2p16), D6S275 (6q15-q16), D6S457 (6q21-q23.2), D9S304 (9p21), D9S157 (9p23-p22), D10S212 (10q26.12-13), D11S2000 (11q22-q23), D13S153 (13q14), D17S786 (17p13), and D17S1322 (17q21). The heterozygosity of these markers ranged from 20% to 62% in published studies (Bengoechea-Beeby et al, 1993; Thompson et al, 1995; Shirasaki et al, 2001; Pollock et al, 2003;) and from 61% to 92% according to the Centre d’Etude du Polymorphisme Humain (CEPH) database (version v2.1 last accessed on April 8 th 2008). The following 6 markers with heterozygosities between 69% and 87% (CEPH) have not been previously tested in melanomas but were selected because they map to chromosomal arms found by Curtin et al (2005) to be altered : D6S1043 (6q16), D7S1824 (7q34), D8S1104 (8p11), D10S676 (10q22), D11S1998 (11q23), and a pentanucleotide repeat within the TP53 gene (17p13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of these markers map to 8 different chromosomes and have previously shown a high incidence of LOH or MSI (>30%) either in primary or metastatic melanomas (35,46-48): D1S214 (1p36.3), D2S2182 (2p16), D2S2291 (2p16), D6S275 (6q15-q16), D6S457 (6q21-q23.2), D9S304 (9p21), D9S157 (9p23-p22), D10S212 (10q26.12-13), D11S2000 (11q22-q23), D13S153 (13q14), D17S786 (17p13), and D17S1322 (17q21). The heterozygosity of these markers ranged from 20% to 62% in published studies (Bengoechea-Beeby et al, 1993; Thompson et al, 1995; Shirasaki et al, 2001; Pollock et al, 2003;) and from 61% to 92% according to the Centre d’Etude du Polymorphisme Humain (CEPH) database (version v2.1 last accessed on April 8 th 2008). The following 6 markers with heterozygosities between 69% and 87% (CEPH) have not been previously tested in melanomas but were selected because they map to chromosomal arms found by Curtin et al (2005) to be altered : D6S1043 (6q16), D7S1824 (7q34), D8S1104 (8p11), D10S676 (10q22), D11S1998 (11q23), and a pentanucleotide repeat within the TP53 gene (17p13).…”
Section: Methodsmentioning
confidence: 99%
“…The strongest evidence in favor of a primary tumor is the presence of an associated precursor lesion (melanocytic nevus or in situ melanoma). Additional criteria to differentiate metastatic and primary lesions include location, grouping, invasion of lymphatic capillaries, and presence of a brisk inflammatory cell infiltrate, although some of these characteristics may be shared by both primaries and metastatic melanomas (Heenan and Clay, 1991; Bengoechea-Beeby et al, 1993). For pathologists familiar with the spectrum of pathologic features of melanocytic tumors it is usually not difficult to establish a pathologic diagnosis of primary cutaneous melanoma, particularly if the diagnosis is made in the context of an appropriate clinical history.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the original description, multiple reports have described the varied histopathologic presentations of epidermotropic metastatic melanomas, proposed additional criteria, and questioned whether histopathology alone can differentiate these metastases from a new primary melanoma. [5][6][7][8][9][10][11][12] Molecular studies of melanoma and its metastases in various forms have revealed frequent genetic alterations. Traditional ideology infers that tumors result when a single transformed cell leads to a clonal population of malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] This phenomenon has been acknowledged only relatively recently; series of cases addressing the problem have appeared only during the past 25 years. Before that time, several microscopic features of melanocytic lesions, such as intraepidermal growth, the lack of a "grenz" zone in the dermis, and involvement of dermal appendages, were touted as useful in identifying such tumors as primary.…”
mentioning
confidence: 99%
“…Since then, other reports have solidified their observations. [1][2][3][4][5][6] It is recognized that secondary melanomas in the skin cannot be distinguished reliably from lesions arising there, because they potentially share literally all of the histologic features of primary melanocytic tumors. As summarized by White and Hitchcock, 6 these characteristics include an ability for epidermotropic growth beyond the lateral confines of a dermal component, formation of epidermal collarettes around nodules in the corium, intravascular tumor cell aggregates, tumor symmetry, nevoid cytologic features, apparent dermal "maturation," and an ability for solely intraepidermal growth with the appearance of in situ melanoma.…”
mentioning
confidence: 99%